2016
DOI: 10.1590/0102-33062015abb0290
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of babassu palm ( Attalea speciosa Mart.) in the Tucuruí Lake Protected Areas Mosaic - eastern Amazon

Abstract: Documenting the ethnobotanical knowledge of populations living in protected areas is important both for science and for the eff ective conservation of these areas, as it can help to clarify the level of dependency that human communities have on local plant resources. Babassu (Attalea speciosa, Arecaceae) is one of the most important non-timber forest resources of rural communities in the Amazon. We explored the ethnobotanical knowledge and uses of babassu by riverine populations inhabiting the Tucuruí Lake Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The species is widespread and economically important, especially in Maranhão, a state in northeastern Brazil. The fruit is exploited as an energy source, food, or medicine, while the seeds obtained by manual breaking of the fruit are transformed into oil [2][3][4].…”
Section: Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The species is widespread and economically important, especially in Maranhão, a state in northeastern Brazil. The fruit is exploited as an energy source, food, or medicine, while the seeds obtained by manual breaking of the fruit are transformed into oil [2][3][4].…”
Section: Featuresmentioning
confidence: 99%
“…Populations inhabiting the Tucuruí Lake Protected Areas in the eastern Amazon use the oil for skin infections, myiasis, and mycosis. In addition, they use it as hair moisturizing agent, and, curiously, the oil from the beetle Pachymerus nucleorum larva, which develops inside the seed of the coconut, is also used for the same purpose [4].…”
Section: Dermatologic and Cosmetic Usesmentioning
confidence: 99%
“…In Brazil, local human populations heavily harvest the fruits and leaves of babassu palm, Attalea speciosa, for human and animal food, as well as for artisanal, construction, medicinal, cosmetic and commercial purposes, mainly in the North and Northeast regions of the country (Balick 1984;Rufino et al 2008;Souza et al 2011;González-Pérez et al 2012;Campos et al 2015;Araújo et al 2016). This species can occur isolated in forests or in areas used for agriculture or pasture, and is considered a pioneer and dominant species in anthropically altered areas because it is an efficient colonizer (Ribeiro & Walter 1998;Mitja & Ferraz 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabic language, it is called Ghadaf or Sa'f [22]; Mazri palm in English [27]; Merez in Afghani Pashto [43]; Patha in Balochistani Pashto [23]; Mazri in Saraiki [18]; Purk in Persian [44]; Daz in Balochi [24]; Mezaray in Malakand, Swat, Dir, Bajaur, and Mardan ares were Pashto is spoken [16]; Mazara in the Bannu Pashto [15]; and Mazarai in South Waziristan Pashto [13]. The palm family is one of the richest families in terms of fiber-producing plants and several researchers reported a broad variety of uses of different palm taxa in different wolrdwide regions; for example, [37] reported that the natives of Tucurui Lake in the Eastern Amazon use Attalea speciosa (Babassu) palm for utensils, tools, human food, animal fodder, construction, fuel, and medicines. Uses of Attalea speciosa reflects similarities to our findings linked to Nannorrhops ritchiana in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed both qualitatively and quantitatively for having a pattern of use of Mazri palms among the various ethnic groups considered in both focus groups. Uses of different items prepared from Mazri palm in the areas from where it was collected and the regions from where its use was documented during the market survey were arranged in a table [37,38].…”
Section: Data Analysesmentioning
confidence: 99%